Patterns of Prescription in a Psychiatry Out Patient Department in a Teaching Hospital in Bangladesh - Any, Omma Hafsa; Parveen, Feroza; Ara, Ferdous; Iqbal, Mohammad Ju; Saha, Rekha Rani (Bangladesh Journal of Physiology and Pharmacology, 2014)
A cross-sectional descriptive study was carried out among individuals attending the psychiatry out-patient department from February 1st 2010 to April 30th 2010 in Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh to see the patterns of prescription and drug use in psychiatry out-patient department of teaching hospital in Bangladesh.A total of 300 patient were included in this study. The average number of drugs per encounter was 2.44 drugs were prescribed by generic name. The commonest clinical indication were schizophrenia and other psychotic disorder (40%) and use of psychotropic drug (36%) frequently but injection use(8.33%) was very low, additional (anticholinergic) drugs were prescribed 76% of prescription. Average cost of drugs per prescription was 181 taka. So, the study will help to understand the trends in prescribing psychotropic drugs and will provide guidelines for designing appropriate future intervention strategies in order to promote rational prescribing and improve the quality of health care. DOI: http://dx.doi.org/10.3329/bjpp.v28i1-2.20076 Bangladesh J Physiol Pharmacol 2012; 28(1&2):19-22